Classification of border subregions of Eastern Poland according to theIR level of socio-economic development (Polityki Europejskie, Finanse i Marketing)
The paper presents the classification of subregions (NUTS 3) with permanent border crossings, in terms of the level of socio-economic development in 2008-2018. The study covered 9 subregions located in the following provinces: Warminsko-Mazurskie, Podlaskie, Lubelskie and Podkarpackie. Application of Hellwig's measure of development made it possible to group subregions according to three categories of the level of development: high, medium and low. The relatively high level of development characterized two metropolitan subregions: Olsztyński and Białostocki. Łomżyński subregion proved to be the weakest, but it was not completely devoid of any development potential. In comparison with the average values in the designated higher development classes, Łomżyński subregion was characterized by: positive natural increase, low values of indices describing ageing of local society and proportion of investment expenditure of local self-government units at a level similar to the leaders of the ranking. However, there is a concern that the relatively low level of spending of the EU funds and the persistent trend of population migration outflow, due to global trends of population ageing and depopulation of rural areas, may negatively affect the socio-economic situation of the subregion in the future.